Faunistic and systematic studies on the Lepturini (Coleoptera: Cerambycidae, Lepturinae) in the Aegean region of Türkiye - Şi̇mşek, Burcu Şabanoğlu; Türkmen, Senem Özdemi̇r; Sert, Osman (Zootaxa, 2024)
In the present study, which is part of a research project examining the Cerambycidae fauna of the Aegean Region of Türkiye (including the provinces of Afyonkarahisar, Aydın, Denizli, İzmir, Kütahya, Manisa, Muğla, Uşak, and southern Balıkesir), Lepturini species (Lepturinae: Cerambycidae) are discussed in both faunistic and systematic terms. A total of 22 species are presented, six of which are new records for the Aegean Region. Additionally, a new species, Stenurella afyoncayensis sp. nov., is described from Afyonkarahisar province. The description of the new species, including photographs of its habitus and genitalia, as well as a differential diagnosis, is provided. Previous records from the study area are compared with and evaluated against our findings. The morphological structures of seven male aedeagus and three spermathecae are described, and detailed drawings are presented for the first time. Furthermore, species identified in previous studies are compared with the current fauna, and a discussion is included regarding whether species not found in the current study may have been affected by climate change.